2020
DOI: 10.1155/2020/2013148
|View full text |Cite
|
Sign up to set email alerts
|

Division of Myocardial Enzyme Reference Intervals in Population Aged 1 to <18 Years Old Based on Fisher’s Optimal Segmentation Method

Abstract: Background. Reference interval (RI) research is to make it a concise, effective, and practical diagnostic tool. This study aimed to establish sex- and age-specific RI for myocardial enzyme activity in population aged 1–<18 years old in Changchun, China. Methods. Healthy subjects (n = 6,322, 1–<18 years old) were recruited from communities and schools. Aspartate aminotransferase (AST), lactate dehydrogenase (LDH), creatine kinase (CK), and creatine kinase isoenzyme (CKMB) were measured using an automatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In fact, our research group has conducted some studies in the early stage, and the results confirm that age, sex, and statistical methods have a certain influence on the reference interval. 3 , 4 Therefore, establishing accurate RIs for local laboratories is one of the most important factors for clinical diagnosis.…”
mentioning
confidence: 99%
“…In fact, our research group has conducted some studies in the early stage, and the results confirm that age, sex, and statistical methods have a certain influence on the reference interval. 3 , 4 Therefore, establishing accurate RIs for local laboratories is one of the most important factors for clinical diagnosis.…”
mentioning
confidence: 99%
“…Previous research has found that the differences in RIs of analytes are due to their complex patterns of biological sources of variations, such as region, race, diet, and more individual characteristic [1,2]. Data from the studies we have published con rms that establishing age-and sexappropriate local RIs is more accurate and reliable for providing clinical decision support, especially in pediatrics [3][4][5][6].…”
Section: Introductionmentioning
confidence: 86%
“…Fisher's ordered partitioning is widely used and has been studied by many scholars at home and abroad. Wenjia Guo, Qi Zhou et al (2020) [59] partitioned the cardiac enzyme reference intervals based on Fisher's ordered partitioning method. Fisher's ordered partitioning method performs well in terms of multidimensionality, and the limitation is that the effect of partitioning on the whole interval should be studied in depth in the future.…”
Section: Fisher Ordered Segmentationmentioning
confidence: 99%